Design of Fire Detector with Water Sprinkler Based on Internet of Things (IoT) - Juliaz, Deal Alfi; Maulana, Halim (Ilmu Bersama Center, 2025)
Fire detectors with smoke and fire sensors integrated with Internet of Things (IoT)- based sprinkler systems are an important innovation in modern fire safety systems. The system combines sensor technology to detect smoke and fire in real-time, as well as an automatic mechanism to respond to danger by spraying water through sprinklers connected to the IoT network. By utilizing IoT, the system can send alerts to mobile devices and control centers directly when a fire is detected, enabling quick response and efficient coordination. This research discusses the design, implementation, and evaluation of this fire detector system, as well as its benefits in improving safety and reducing fire damage. Evaluations were conducted with simulated fires to test the detection accuracy and response effectiveness of the system, demonstrating significant potential in fire risk mitigation and property protection. Hardware design of fire monitoring equipment with water sprinklers based on the Internet of Things (IoT) using NodeMCU ESP8266, Liquid Crystal Display (LCD), Relay, and water sprinklers. The design of the hardware work stages can be seen in the following block diagram.